P Pengaruh Konsentrasi Carbopol 940 dan Paraffin Liquid terhadap Evaluasi Sediaan Serum Emulgel Ekstrak Pegagan (Centella asiatica (L.) Urban) Sebagai Anti Jerawat - Kasmayuda, Muhammad; Audina, Mia; Mahdiyah, Dede; Noval, Noval (Jurnal Pelayanan Kefarmasian dan Sains, 2024)
Background: Acne is a health problem on the skin that is often experienced by everyone. Acne or acne is a skin disease that is common in all ages, from teenagers to adults. Pegagan (Centella asiatica (L.) Urban) is a plant that has antibacterial properties to treat acne-causing bacteria. Emulgel serum is a liquid preparation that has a high concentration of active ingredients on a combination basis of emulsion and gel.Objective: Identify formulations of various concentrations of carbopol 940 and liquid paraffin based on the evaluation results of anti-acne emulgel preparations of Centella asiatica extract and analyze the effect of variations in concentrations of carbopol 940 and paraffin liquid on the evaluation of anti-acne emulgel preparations of Centella asiatica extract.Methods: The research method used was experimental and the research design carried out was with treatment or intervention which then carried out a quasi-experimental design with a non-equivalent control group design and one group posttest-only design.Results: The results showed that the serum emulgel extract of Centella asiatica (L.) Urban) with various concentrations of carbopol 940 and paraffin liquid showed an effect on organoleptic, pH, spreadability, adhesion, and viscosity.Conclusion: Of the three formulas in the preparation of gotu kola extract serum emulgel preparations with various concentrations of carbopol 940 and liquid paraffin, from the results of all physicochemical evaluations, the best results were obtained in formula 3.